Utilizing Internet of Things (IOT)-based Design for Consumer Loyalty: A Digital System Integration - Zaenal Aripin; Vip Paramarta; Kosasih (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to describe the design of a digital system to create IOT-based customer loyalty. The application of IOT systems for the banking sector is inevitable as part of the widespread positive impact of communication and information technology. The method used in this research is to use literature review by reading a lot of previous research which is the basis for this research by reading a lot of research, the author will be able to better understand the ongoing research by reading a lot of books and journals of previous research, new problems will be found and can be used as future research. The result of this research is a proposed system that can be used as a reference for further research, and can be used as an applied system so that the existing system can be further developed and can be even better, the proposed system produces the latest system using IoT and is expected to produce a smart consumer loyalty system.Â